Rescue of murine F508del CFTR activity in native intestine by low temperature and proteasome inhibitors. - Martina Wilke; Alice Bot; Huub Jorna; Bob J Scholte; Hugo R de Jonge (PLoS ONE, 2012)
Most patients with Cystic Fibrosis (CF) carry at least one allele with the F508del mutation, resulting in a CFTR chloride channel protein with a processing, gating and stability defect, but with substantial residual activity when correctly sorted to the apical membranes of epithelial cells. New therapies are therefore aimed at improving the folding and trafficking of F508del CFTR, (CFTR correctors) or at enhancing the open probability of the CFTR chloride channel (CFTR potentiators). Preventing premature breakdown of F508del CFTR is an alternative or additional strategy, which is investigated in this study. We established an ex vivo assay for murine F508del CFTR rescue in native intestinal epithelium that can be used as a pre-clinical test for candidate therapeutics. Overnight incubation of muscle stripped ileum in modified William's E medium at low temperature (26°C), and 4 h or 6 h incubation at 37°C with different proteasome inhibitors (PI: ALLN, MG-132, epoxomicin, PS341/bortezomib) resulted in fifty to hundred percent respectively of the wild type CFTR mediated chloride secretion (forskolin induced short-circuit current). The functional rescue was accompanied by enhanced expression of the murine F508del CFTR protein at the apical surface of intestinal crypts and a gain in the amount of complex-glycosylated CFTR (band C) up to 20% of WT levels. Sustained rescue in the presence of brefeldin A shows the involvement of a post-Golgi compartment in murine F508del CFTR degradation, as was shown earlier for its human counterpart. Our data show that proteasome inhibitors are promising candidate compounds for improving rescue of human F508del CFTR function, in combination with available correctors and potentiators.